An An Analysis of Anxiety in Speaking Class Among Students at BEC Academy in Learning English - Ni Ketut Mangku; I Gede Budasi; Dewa Putu Ramendra (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This research investigates speaking anxiety among students at BEC Academy, where oral communicative ability is highly associated with related to professional preparation. The study aims to evaluate (1) the level of students’ speaking anxiety, (2) the factors contributing to their anxiety, and (3) the instructional strategies employed by the English instructor to reduce anxiety during speaking activities. A mixed method research design was implemented. Quantitative data were collected using the Foreign Language Classroom Anxiety Scale (FLCAS) administered to 19 students, while qualitative data were obtained through classroom observations and semi structured interviews with selected students and the instructor. The findings reveal three main results. First, the majority of students experienced moderate speaking anxiety. Out of 19 students, 12 students (63.2%) were categorized as having a moderate level of speaking anxiety, 6 students (31.6%) were classified as having a high level of anxiety, only 1 student (5.3%) demonstrated a low level of speaking anxiety. Second, the factors contributing to students’ speaking anxiety include fear of making mistakes and negative evaluation, anxiety triggered by specific speaking tasks, influence of classmates, instructors and classroom atmosphere, self-confidence and negative self-perception, influence of past negative experiences, linguistics difficulties and language complexity, and external and situational factors. Third, this study found that the instructor implemented several strategies to reduce anxiety, including creating a supportive classroom atmosphere, providing positive reinforcement, using pair-based role play, providing scaffolding and structured preparation, applying delayed corrective feedback, and adjusting instructional tasks based on students’ observable emotional responses.